Methodology of Development of Account Information Systems - Prastiwi, Ella; Hazmi, Yusri; Putri, Siti Muthmainnah; Farabi, M Iqbal (Eastasouth Institute, 2024)
System development methodology is the framework used to design, develop, and implement information systems. Accounting Information Systems (SIAs) play an important role in managing financial and operational data within an organization. Effective SIA development requires structured and systematic methodology. The method used is descriptive qualitative. This article discusses a variety of SIA development methodologies, including Waterfall, Agile, and DevOps. (Development and Operations). The aim of this article is to evaluate the advantages and disadvantages of each methodology and provide guidance for developers and project managers in choosing the methodology that best suits their organization's needs.